Pengaruh paparan twitter terhadap penguasaan bahasa inggris dalam tinjauan literatur - Ranu, Andarini (Maliki Interdisciplinary Journal, 2025)
Twitter has become one of the most popular social media platforms among students, including those learning English as a foreign language (EFL). This article aims to examine the extent to which Twitter contributes to English language proficiency, particularly in terms of vocabulary, writing skills, and student engagement. Using a literature review method, the author examined a number of relevant and credible scientific articles to assess the impact of Twitter exposure on English language development among young people. The findings indicate that Twitter use has the potential to enhance English language proficiency through exposure to authentic input, the use of informal language and slang, and digital social interactions that promote contextual language learning. This article highlights that Twitter is not merely a communication platform but also an effective language learning tool when used wisely and strategically.